PENGARUH LATIHAN BARRIER HOPS DAN KNEE TUCK JUMP TERHADAP POWER TUNGKAI PADA KLUB BOLA VOLI MASTER VOLI BALL CLUB - Aprinda Putra Anggara; Donny Anhar Fahmi; Agus Wiyanto (STKIP Subang, 2024)
This research was based on volleyball athletes who were masters of ball club volleyball when they did a less than optimal jump smash, as well as when they blocked the opponent's smash range was higher than their block so it was very easy to penetrate. This research was conducted using a quantitative approach using a preexperimental design method with a two-group pretest-posttest design. The sample in this research was 20 volleyball master ball club volleyball athletes. The research results were then processed using IBM SPSS 23 and a paired sample t test was carried out showing that the mean result of the pretest and posttest barrier hops was 93.70 to 100.40. The paired sample Ttest hypothesis test on the pretest data and posttest data obtained a sig (2-tailed) value. ) 0.005. Meanwhile, the knee tuck jump result was 93.10 to 99.00. The paired sample T-test hypothesis test on pretest data and posttest data obtained a sig (2-tailed) = 0.002. Based on the research results, the application of barrier hops and knee tuck jump exercises has an effect on increasing leg power and barrier hops exercises are more efficient on leg power at the Master Volleyball Club volleyball club and in subsequent research to be able to develop leg power in volleyball with different variables.